1985
DOI: 10.4319/lo.1985.30.3.0489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and plant source on lignocellulose biodegradation rates in two wetland ecosystems, the Okefenokee Swamp and a Georgia salt marsh1,2,3

Abstract: The microbial mineralization of synthetic [ L4C]lignin, specifically radiolabeled [ 14C-ligninl-lignocellulose and [ L4C-polysaccharide]-lignocellulose from a variety of aquatic herbaceous and woody plants was investigated in water and sediment from a salt marsh on Sapelo Island, Georgia, and from the Okefenokee Swamp, an acidic peat-forming freshwater swamp in southern Georgia. Rates of microbial degradation of lignocellulose were depressed in the Okefenokee relative to those in the salt marsh. About 50% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 22 publications
2
34
0
2
Order By: Relevance
“…Thus, over this period of decomposition, these results are consistent with those of Marinucci et al (1983). Similarly, Benner et al (1985) found a strong positive correlation between initial nitrogen content of several plant species, including S. alterniflora, and rates of lignocellulose decomposition over the course of a 1 mo laboratory incubation experiment.…”
Section: Relation Of Initial Substrate Quality To Decaysupporting
confidence: 79%
“…Thus, over this period of decomposition, these results are consistent with those of Marinucci et al (1983). Similarly, Benner et al (1985) found a strong positive correlation between initial nitrogen content of several plant species, including S. alterniflora, and rates of lignocellulose decomposition over the course of a 1 mo laboratory incubation experiment.…”
Section: Relation Of Initial Substrate Quality To Decaysupporting
confidence: 79%
“…Early studies suggested that the lignin polymer was essentially inert in the absence of oxygen (Hackett etal., 1977). However, it has since been shown that the complex lignin polymer can undergo anaerobic degradation (Benner et al, 1985(Benner et al, , 1986, but the process can be rather slow and tends to yield unmetabolized products (Colberg and Young, 1982;Young and Frazer, 1987). Anaerobic loss of lignin polymers is -3-30% as complete as aerobic degradation of the same polymers (Benner et al, 1984); the cellulose component is more labile than the lignin component.…”
Section: Ligninmentioning
confidence: 99%
“…Organic matter deposited in near-shore marine and most freshwater habitats is composed primarily (-75% by weight) of lignocellulose, a complex mixture of lignin and the polysaccharides cellulose and hemicellulose (Benner et al, 1985). Lignin is a unique phenolic polymer of nonrepeating units that makes up 25-30% of the biopolymers in vascular plants and is second only to cellulose as the most abundant organic carbon source in the biosphere.…”
Section: Ligninmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of complex organic molecules to simpler organic and inorganic constituents by various processes such as abiotic leaching (Harrison and Mann, 1975;Benner et al, 1985), fragmentation (Boulton and Boon, 1991), extracellular enzymatic hydrolysis (Cunningham and Wetzel, 1989), and aerobic and anaerobic catabolic activities of microorganisms could occur depending on environmental conditions, and export or recycle through the ecosystems. Learning the resilience and threshold levels allows to gauge the strengths and weaknesses of our technological advancement and policies to tackle adversities of hydro-climatic changes to many ecosystems including aquatic and semi-aquatic ones.…”
Section: Introductionmentioning
confidence: 99%